Litostratigrafia do Terciario da região Miranda do Corvo-Viseu (Bacia do Mondego, Portugal) - Cunha, Pedro Proença (2010)
The lithostratigraphic units (2 groups, 5 formations and 4 members) of the Tertiary of the Miranda do Corvo-Viseu region (Central Portugal) are here described. For each unit the characterization and description (boundaries, diagnostic properties and atributes) were included. The stratigraphic, lithological, sequential and tectonic data allow correlations with other units of the same Tertiary basin located more to west and support the chronostratigraphic attribution. Sedimentologic characteristics of the deposits lead to the interpretation of the influence of tectonism, climate and eustasy during the sedimentary evolution of this Basin.